Liver steatosis is a major predictor of poor outcomes in chronic hepatitis C patients with sustained virological response. Issue 11 (17th July 2019) - Peleg, Noam; Issachar, Assaf; Sneh Arbib, Orly; Cohen‐Naftaly, Michal; Harif, Yael; Oxtrud, Evelin; Braun, Marius; Leshno, Moshe; Barsheshet, Alon; Shlomai, Amir
Abstract: Sustained virological response (SVR) results in reduced incidence of hepatocellular carcinoma (HCC) and mortality among chronic hepatitis C (CHC) patients with advanced fibrosis. Since both advanced fibrosis and liver steatosis (LS) may coexist in CHC patients, we evaluated their individual effects on a composite outcome of all‐cause mortality and HCC in CHC patients with SVR following direct‐acting antivirals (DAA) treatment. We retrospectively evaluated inception cohort of 515 CHC patients who achieved SVR following treatment with DAA, with a mean follow‐up of 24 months. Baseline liver fibrosis was assessed by transient elastography, and LS was validated by at least three independent ultrasonographic examinations. 211 of 515 patients (41%) had baseline LS. Patients with LS had a higher cumulative rate of all‐cause mortality and HCC at 2 years of follow‐up compared to patients without LS (15.75% and 2.79%, respectively, P  < 0.001), although they did not have increased incidence of advanced fibrosis or cirrhosis. Consistently, multivariate analysis showed that LS was associated with a significant 7.5‐fold increased risk of all‐cause mortality and HCC (HR 7.51, 95% C.I 3.61‐13.36, P  < 0.001) even upon adjustment to components of the metabolic syndrome, whereas advanced fibrosis showed only a trend towards statistical significance (HR 2.32, 95% C.I 0.97‐6.59, P  = 0.06). In conclusion, LS is a major predictor of all‐cause mortality and HCC in patients who achieved SVR following DAA treatment regardless of fibrosis stage. These patients should be rigorously screened for HCC.